A Comparative Study Of The Function Of Small Talk Between Arab And Malay Communication - Mohamad, Norhayuza; Mamat, Anis Nabilah; Zakaria, Muhamad Zaidi; Puasa, Bashasunnahar; Mohd Ramli, Zuraini (Ijaz Arabi Journal of Arabic Learning, 2023)
Small talk is defined as an informal dialogue or conversation that does not cover an important topic of conversation. It is a polite conversation about insignificant matters. To date, the small talk function of Arab and Malay communication has not been clearly understood due to a lack of research in this field. This study compares the part of small talk in Arab and Malay communication based on three communication phases: beginning, middle, and closing. The study is descriptive and employs a qualitative approach. The data from the small talk was analyzed using Malinowski's Phatic Communion Theory (1923). The researchers obtained data from an Arabic drama called "أوراق الزمن المر" and a Malay drama called "Nur 2". ATLAS.tiV9 was used to analyze and code small talk expressions. The findings revealed similarities and differences in the small talk function used in each conversation phase between Arab and Malay communication. Regarding the use of small talk in the middle stage of communication, the Arab and Malay communities are similar. Among the differences, the Arab community was discovered to like to interrupt conversations with small talk while having a conversation. In contrast, the Malay community rarely interrupts conversations with small talk while interacting. Overall, this study discovered that the Arab community demonstrated a broader function of small talk than the Malay community. This study will likely benefit both the field of intercultural communication as well as the use of small talk in learning and teaching Arabic as a foreign language.